Tìm GTLN hoặc GTNN của các đa thưc sau: a, -x^2 + 2x + 3 b, x^2 – 2x + 4y^2 – 4y + 8 c, -x^2 – y^2 + xy + 2x + 2y + 4 d, x^2 + 5y^2 – 4xy – 2y + 20

By Gianna

Tìm GTLN hoặc GTNN của các đa thưc sau:
a, -x^2 + 2x + 3
b, x^2 – 2x + 4y^2 – 4y + 8
c, -x^2 – y^2 + xy + 2x + 2y + 4
d, x^2 + 5y^2 – 4xy – 2y + 2015
e, 2x^2 + y^2 + 6x + 2y + 2xy + 2018

0 bình luận về “Tìm GTLN hoặc GTNN của các đa thưc sau: a, -x^2 + 2x + 3 b, x^2 – 2x + 4y^2 – 4y + 8 c, -x^2 – y^2 + xy + 2x + 2y + 4 d, x^2 + 5y^2 – 4xy – 2y + 20”

  1. Đáp án:

    $\begin{array}{l}
    a)A =  – {x^2} + 2x + 3\\
     =  – \left( {{x^2} – 2x – 3} \right)\\
     =  – \left( {{x^2} – 2x + 1 – 4} \right)\\
     =  – {\left( {x – 1} \right)^2} + 4\\
    Do: – {\left( {x – 1} \right)^2} \le 0\\
     \Rightarrow  – {\left( {x – 1} \right)^2} + 4 \le 4\\
     \Rightarrow GTLN = 4\,khi:x = 1\\
    b){x^2} – 2x + 4{y^2} – 4y + 8\\
     = {x^2} – 2x + 1 + 4{y^2} – 4y + 1 + 6\\
     = {\left( {x – 1} \right)^2} + {\left( {2y – 1} \right)^2} + 6 \ge 6\\
     \Rightarrow GTNN = 6\,khi:\left\{ \begin{array}{l}
    x = 1\\
    y = \frac{1}{2}
    \end{array} \right.\\
    c) – {x^2} – {y^2} + xy + 2x + 2y + 4\\
     =  – \frac{1}{2}.\left( {2{x^2} + 2{y^2} – 2xy – 4x – 4y – 8} \right)\\
     =  – \frac{1}{2}.\left( \begin{array}{l}
    {x^2} – 2xy + {y^2} + {x^2} – 4x + 4\\
     + {y^2} – 4y + 4 – 8 – 8
    \end{array} \right)\\
     =  – \frac{1}{2}.\left[ {{{\left( {x – y} \right)}^2} + {{\left( {x – 2} \right)}^2} + {{\left( {y – 2} \right)}^2}} \right] + \frac{1}{2}.16\\
     =  – \frac{1}{2}\left[ {{{\left( {x – y} \right)}^2} + {{\left( {x – 2} \right)}^2} + {{\left( {y – 2} \right)}^2}} \right] + 8 \le 8\\
     \Rightarrow GTLN = 8\\
    Khi::x = y = 2\\
    d){x^2} + 5{y^2} – 4xy – 2y + 2015\\
     = {x^2} – 4xy + 4{y^2} + {y^2} – 2y + 1 + 2014\\
     = {\left( {x – 2y} \right)^2} + {\left( {y – 1} \right)^2} + 2014 \ge 2014\\
     \Rightarrow GTNN = 2014\\
    Khi:x = 2y = 2\\
    e)2{x^2} + {y^2} + 6x + 2y + 2xy + 2018\\
     = {x^2} + {y^2} + 1 + 2xy + 2y + 2x\\
     + {x^2} + 4x + 4 + 2013\\
     = {\left( {x + y + 1} \right)^2} + {\left( {x + 2} \right)^2} + 2013 \ge 2013\\
     \Rightarrow GTNN = 2013\\
    Khi:\left\{ \begin{array}{l}
    x =  – 2\\
    y =  – x – 1 = 1
    \end{array} \right.
    \end{array}$

    Trả lời

Viết một bình luận